2021
DOI: 10.1021/acs.jpca.1c03028
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Transport Parameters Using ab initio and AMOEBA Polarizable Force Field Methods

Abstract: The transport properties of chemical species such as coefficients of diffusion, thermal conductivity, and viscosity have been widely used in combustion modeling. Lennard-Jones parameters fitted from the accurate intermolecular potential energy surfaces are crucial to obtain such information. Hence, a fast and accurate energy function is always desired for this purpose. In this study, the quality of a widely used polarizable force field AMOEBA was examined for the interaction between noble gases and nalkanes. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The collision diameter σ ij in eq 18 can be estimated according to the Lorentz-Berthelot combination rule, 41,42 = + ( )/2 ij ii jj (18) with the ε ij parameter determined by…”
Section: Viscosity Coefficient Of Moleculesmentioning
confidence: 99%
“…The collision diameter σ ij in eq 18 can be estimated according to the Lorentz-Berthelot combination rule, 41,42 = + ( )/2 ij ii jj (18) with the ε ij parameter determined by…”
Section: Viscosity Coefficient Of Moleculesmentioning
confidence: 99%
“…Previous studies have demonstrated that N = 2000 directions in the L-J parameters by the ODM method showed good convergence . Hence, N = 2000 was used in the present work.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Previous studies have demonstrated that N = 2000 directions in the L-J parameters by the ODM method showed good convergence. 36 Hence, N = 2000 was used in the present work. In addition, to make the points uniformly distributed on the sphere, the bath gas positions were derived using the Marsaglia method.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations